Biomedical Data Mining for Information Retrieval 2021
DOI: 10.1002/9781119711278.ch8
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Image Analysis of Drying Bovine Serum Albumin Droplets in Phosphate Buffered Saline

Abstract: A bio-colloidal drying droplet can be used as a pre-diagnostic technique. However, a successful clinical setting requires a fundamental understanding of the final morphology and the way it is related to the initial state of the constituents present in the droplet. This chapter focuses on the physics associated with different pattern formations in the globular protein, bovine serum albumin (BSA) at different phosphate buffered saline concentrations. The study reports that the first-order statistics (FOS) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…However, the behavior of the droplets at both 0 and 75%(v/v) concentrations is distinct and noteworthy. These observations are consistent with previous findings in the realm of bio-colloids [45-46], indicating the broader applicability of the observed phenomena. Regardless of whether water or PBS is added, the drying process follows a consistent pattern in terms of its stages: an initial stage , a middle stage (∼ 0.5 − 0.8), and a final stage (∼ 0.8 − 1.0).…”
Section: Resultssupporting
confidence: 93%
“…However, the behavior of the droplets at both 0 and 75%(v/v) concentrations is distinct and noteworthy. These observations are consistent with previous findings in the realm of bio-colloids [45-46], indicating the broader applicability of the observed phenomena. Regardless of whether water or PBS is added, the drying process follows a consistent pattern in terms of its stages: an initial stage , a middle stage (∼ 0.5 − 0.8), and a final stage (∼ 0.8 − 1.0).…”
Section: Resultssupporting
confidence: 93%
“…The study explored the evolution of the final state of drying BSA-lysozyme films in NaCl salts' presence using the FOS and GLCM techniques. Pal et al [28] also examined BSA drops at different initial concentrations of phosphate buffer saline (PBS). The statistical analysis incorporated in that work showed that these GLCM parameters' horizontal and vertical orientations have a non-significant effect when the pixel displacement is ≤1.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has also established a new processing tool to determine the distance between the consecutive cracks [100]. The texture of the images could also be quantified using FOS and GLCM statistical parameters [95,198,199]. The FOS is based on the gray-level distribution of the pixel values without intervening in the interpixel relationships.…”
Section: B Image Processing Techniques and Machine Learning Algorithmsmentioning
confidence: 99%
“…These parameters can also be compared using parametric or non-parametric statistical models. For example, it is shown how these GLCM parameters significantly depend on the horizontal and vertical orientations of the neighboring pixels in an image [198]. Therefore, it cannot be averaged or generalized for all the systems.…”
Section: B Image Processing Techniques and Machine Learning Algorithmsmentioning
confidence: 99%